PENGARUH FAKTOR-FAKTOR PENDUKUNG DAN PENGHAMBAT PERAN DAN ORIENTASI PEMERINTAH DAERAH DALAM RANGKA MENGOPTIMALKAN PENDAPATAN DAERAH (Survey pada Pemerintah Propinsi Jawa Barat)1 - Memen Kustiawan2 (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2006)
It is a study on Public Sector Accounting, i.e. examining the role and orientation of the local government in response to the encouraging and obstructive factors in optimizing the local revenue. The objectives of this research are to recognize: (1) the influence of the encouraging and obstructive factors upon the role and orientation the local government, (2) the influence of encouraging and obstructive factors upon the local revenue, (3) the role of the local government in enhancing the local revenue, and (4) the dominant componentsof encouraging and obstructive factors. The unit of analysis is the Local Government of West Java Province. The respondents for this research are the elements of analysis units, namely 31 service units of local revenue(UPPD) which are divided based on the regions spread all over West Java Province. On top of that, an interview is carried out with some decision makers of the local government (based on the organizational structures), namely: (1) the Secretariat of Local Government and (2) Local Service Department. In addition to the circulation of the questionnaire and interview, an observation is also conducted. Data analysis is conducted in two ways, namely the quantitative and qualitative approaches. Firstly, the quantitative approach consists of 2 methods, namely the path and correlation analysis. Secondly, the qualitative analysis is based on the theory and rationality and is used to accomplish the quantitative result of the analysis. The result of path and correlation analysis shows that: (1) the role and orientation of local government are positively influenced by encouraging factors (14,80%), and negatively by obstructive factors (8,20%); (2) the local revenue is positively influenced by encouraging factors (0,44%), and negatively influenced by obstructive factors (21,53%); (3) the localrevenue is positively influenced by the local government’s role and orientation (2,68%); (4) dominant components of encouraging factors are tax law and other laws pointed out by correlation coefficient at the value of 0,909, and the most dominant component at the obstructive factors is the collection cost marked by the correlation coefficient at the value of 0,743. This shows that the local government’s role and orientation play a part in raising the local revenue. Whereas, based on the qualitative analysis, the ratio of local revenueagainst the regional gross domestic product from 1999/2000 up to 2004 is around 0.28%- 0.93%. It shows that there is still a potential of local revenue which is yet to be realized by West Java Province.